Pembelajaran Aqidah Akhlaq Dan Kompetensi Guru Mata Pelajaran Implikasinya Terhadap Akhlaq Siswa - Amin, Furkon; Jauhari, Adibah (Universitas Darul Ulum, 2022)
The purpose of this study was to determine the effect of learning Aqidah Akhlak and Aqidah Akhlaq Teacher Competencies on the morals of students of SMK Bisri Syamsuri Denayar Jombang. This research approach is a quantitative approach with an explanation (explanatory research) with a survey method. Aqidah Akhlaq Learning Variable as a variable (X1) and Teacher Competency variable as a variable (X2), Aqhlak as an independent variable (Y). The population amounted to 148 students with Proportional Random Sampling sampling obtained 115 samples from class X, XI and XII. Methods of data collection using questionnaires with an interval scale with a Likert model. This study uses the described quantitative data analysis techniques. The results obtained in this study are the level of Aqidah Akhlaq Learning carrying out Teacher Competency obtained 85% have high Aqidah Akhlaq Learning Aqidah Akhlaq Learning, 15% have Aqidah Akhlaq Learning Aqidah Akhlaq Learning is moderate and there are no students who have Aqidah Akhlaq Learning Aqidah Akhlaq learning is low. Based on the results of statistical analysis and discussion, the level of student morality is obtained, from 9.5% who have a high level of student morality, 27.5% have a moderate level of student morality and 63% have a low level of student morality.